2020
DOI: 10.1038/s41467-020-19033-z
|View full text |Cite
|
Sign up to set email alerts
|

SUSA2 is an F-box protein required for autoimmunity mediated by paired NLRs SOC3-CHS1 and SOC3-TN2

Abstract: Both higher plants and mammals rely on nucleotide-binding leucine-rich repeat (NLR) immune receptors to detect pathogens and initiate immunity. Upon effector recognition, plant NLRs oligomerize for defense activation, the mechanism of which is poorly understood. We previously showed that disruption of the E3 ligase, Senescence-Associated E3 Ubiquitin Ligase 1 (SAUL1) leads to the activation of the NLR SOC3. Here, we report the identification of suppressor of saul1 2 (susa2) and susa3 from the saul1-1 suppresso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 73 publications
(124 reference statements)
0
13
0
Order By: Relevance
“…Silencing of SGT1/RAR1/HSP90 components alleviates autoimmune responses in several autoimmune mutants. For example, SGT1b is a positive regulator of the autoimmune response displayed by chs3 mutants (Xu et al 2015), HSP90.3 is required for the constitutive activation of defense response in the saul1-1 mutant (Liang et al 2020) and topp4-1 autoimmune phenotypes require RAR1 and HSP90.2 (Yan et al 2019). Similarly, the spontaneous cell death and hyperaccumulation of ROS exhibited by plants overexpressing MSL10-GFP required SGT1b, RAR1 , and HSP90 in both tobacco and Arabidopsis ( Figure 3, S2 and S3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Silencing of SGT1/RAR1/HSP90 components alleviates autoimmune responses in several autoimmune mutants. For example, SGT1b is a positive regulator of the autoimmune response displayed by chs3 mutants (Xu et al 2015), HSP90.3 is required for the constitutive activation of defense response in the saul1-1 mutant (Liang et al 2020) and topp4-1 autoimmune phenotypes require RAR1 and HSP90.2 (Yan et al 2019). Similarly, the spontaneous cell death and hyperaccumulation of ROS exhibited by plants overexpressing MSL10-GFP required SGT1b, RAR1 , and HSP90 in both tobacco and Arabidopsis ( Figure 3, S2 and S3 ).…”
Section: Discussionmentioning
confidence: 99%
“…The head-to-head arranged NLR gene pairs have been reported in many studies [ 33 , 38 , 40 , 48 , 49 , 50 , 51 , 52 ]. In this article, we found that there was a large TN - TNL gene cluster on Arabidopsis chromosome 1 and showed the association of TN10 with TNL40TIR and TNL60TIR.…”
Section: Discussionmentioning
confidence: 99%
“…The head-to-head genomic arrangements play important roles in regulating the cooperation of NLR proteins as almost all of the identified paired NLRs are encoded by physically linked genes [ 40 ]. For example, the SOC3-CHS1 pair and SOC3-TN2 pair are the two firstly identified unique NLR pairs formed by a full-length TNL and a truncated TN protein [ 33 , 49 ]. The over-accumulation and disappearance of Arabidopsis E3 ligase SAUL1 are monitored by SOC3-TN2 and SOC3-TN1, respectively [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…tomato strain DC3000 [ 19 ]. The TIR-NB-LRR immune receptor suppressor of CHS1, 2, 3 (SOC3) interacts with CHS1 or TN2 and the SCF complex to regulate innate immunity [ 20 , 21 ]. Recently, the singleton TN, dangerous mix 10 (DM10), was reported to cause severe hybrid necrosis, which is typically induced by a conflict between divergent alleles of immunity genes coming from different parental accessions [ 22 ].…”
Section: Introductionmentioning
confidence: 99%